Laser-induced mechanical bending in azo dye-doped liquid-crystal elastomers - H. Finkelmann (Superficies y vacío, 2006)
Laser-induced deformation (bending) in azo dye-doped liquid-crystal elastomer thick films is demonstrated. We directlymeasure the laser-power-dependent deformation-strength (driving force). The deformation-relaxation time is alsomeasured. We have observed that it recovers within 300 ms after the excitation laser pulse is gone, this gave a constanttime of 75 ms. By estimating the optical electric field value of the laser pulses used in our experiments, we can compareour results with those obtained in polyurethane elastomers studied by the electrostriction technique [1,9]